Prevalence, Severity, and Morphological Patterns of Anaemia Among Tribal Children and Adolescents in Chhotaudepur District, Gujarat: A Community-Based Cross-Sectional Study (GAIMS Journal of Medical Sciences, 2026)
Background: Anaemia disproportionately affects tribal populations in India due to nutritional deficiencies, haemoglobinopathies, and limited healthcare access. Community-level data from tribal districts of Gujarat are lacking.Aims and Objectives: To assess the prevalence, severity, and morphological patterns of anaemia among tribal children and adolescents in Chhotaudepur district, Gujarat, and to evaluate its association with socio-demographic and anthropometric variables.Study Design: Community-based cross-sectional study.Setting: Government residential school, Kawant taluka, Chhotaudepur district, Gujarat, India (February–March 2025).Materials and Methods: A total of 1,478 tribal participants aged 10–20 years were enrolled. CBC was performed on a Sysmex XP-300 analyser; anaemia was classified by WHO 2011 haemoglobin thresholds (age- and sex-stratified) and morphologically by MCV/MCH. Sickling solubility test (2% sodium metabisulphite) was used for haemoglobinopathy screening.Statistics: IBM SPSS v25.0; chi-square, Fisher’s exact, independent t-test, and Spearman correlation; p